2013
DOI: 10.1039/c3cc45091k
|View full text |Cite
|
Sign up to set email alerts
|

A dinitrosyl iron complex as a platform for metal-bound imidazole to N-heterocyclic carbene conversion

Abstract: An N-alkyl imidazole bearing a neutral {Fe(NO)2}(10) dinitrosyliron complex (DNIC) when treated with sodium t-butoxide undergoes base-promoted conversion to the N-heterocyclic carbene (NHC)-DNIC, while maintaining the Fe(NO)2 unit intact. Subsequent alkylation led to the isolation of the NHC-DNIC product; further nitrosylation led to trinitrosyl (NHC)Fe(NO)3(+). Both were isolated and structurally characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…It is noteworthy that the resulting DNIC contains an asymmetric NHC, thereby suggesting this to be a possible route for such syntheses, as well as further conversion to the corresponding TNIC, [(NHCMe-Mes)Fe(NO) 3 ] + by isoelectronic replacement of CO by NO + . 44 This model study demonstrated the impressive stability of the dinitrosyliron unit under base treatment, while supporting the isomerization of metal-bound imidazole to an NHC ligand. To our knowledge, only a few other examples of such interconversions exist in the organometallic literature.…”
Section: Patterns Between Nhc-dnics and Imidazole-dnicsmentioning
confidence: 54%
See 1 more Smart Citation
“…It is noteworthy that the resulting DNIC contains an asymmetric NHC, thereby suggesting this to be a possible route for such syntheses, as well as further conversion to the corresponding TNIC, [(NHCMe-Mes)Fe(NO) 3 ] + by isoelectronic replacement of CO by NO + . 44 This model study demonstrated the impressive stability of the dinitrosyliron unit under base treatment, while supporting the isomerization of metal-bound imidazole to an NHC ligand. To our knowledge, only a few other examples of such interconversions exist in the organometallic literature.…”
Section: Patterns Between Nhc-dnics and Imidazole-dnicsmentioning
confidence: 54%
“…44 The changes that accompanied this process were monitored by IR spectroscopy. As shown in Figure 11, deprotonation at the C2 position of the imidazole ring of 11 by the base resulted in the formation of unstable intermediate species, proposed as 12a/12b.…”
Section: Patterns Between Nhc-dnics and Imidazole-dnicsmentioning
confidence: 99%
“…In 2013 Darensbourg evidenced the occurrence of a base-promoted conversion of a Nalkylimidazole ligand to the corresponding NH-NHC mediated by a dinitrosyl iron complex. 152…”
Section: Scheme 30 Isomerization Of a Benzimidazole Derivative To Itmentioning
confidence: 99%
“…Following with the latter recipe, protic NHCs (pNHCs) consist of the presence of a N-bound H atom. Although most of the studies on NHCs together with metal moieties are based on the interaction of the carbene carbon of the NHC with the metal [ 23 26 ], the high instability due the NH group of the pNHCs can induce secondary interactions leading to bifunctional catalysis [ 27 28 ], substrate recognition [ 29 ] and/or biological systems [ 30 31 ]. Among the synthetic methodologies to access to pNHC metal complexes [ 32 40 ], recently N -arylimine functionalized pNHC iridium complexes were obtained using excess of [Ir(cod)(µ-Cl)] 2 [ 41 ], and next deprotonation of the pNHC leads to an equilibrium between a mononuclear complex containing a C-bound anionic imidazolide [ 42 44 ] and its dimer [ 45 58 ], where the NHC moiety binds in a µ-C,N bridging mode (see Scheme 1 ) [ 44 ].…”
Section: Introductionmentioning
confidence: 99%